Penerapan Technology Acceptance Model (TAM) dalam Adopsi Fintech oleh UMKM di Wilayah Perbatasan Indonesia-Malaysia - Dedy; Sari, Maya; Balang, Fransiskus (Valid: Jurnal Ilmiah, 2025)
The development of financial technology (fintech) plays an important role in supporting the sustainability of Micro, Small, and Medium Enterprises (MSMEs) especially in border areas. The study aims to analyze the factors influencing fintech acceptance by following the Technology Acceptance Model (TAM), focusing on perceived usefulness (PU), perceived ease of use (PEOU), and attitude toward use (ATU) toward behavioral intention to use (BIU). Mixed methods was applied with embedded design involving 90 MSME respondents in Bengkayang as well as in-depth interviews with 12 MSME respondents, including three migrants in the Malaysian border area. Quantitatively, the results show that both PU, PEOU, and ATU positively affect BIU, thus ATU is proven to mediate the relationship between PU and PEOU on BIU. Qualitatively, MSMEs agree with fintech that is beneficial and facilitates, but the obstacles encountered are limitations in infrastructure, financial literacy, and the manual recording by business actors. The findings also indicate the readiness in border areas of Malaysia because facilities such as infrastructure, regulations, and social norms have supported the adoption of technology there, whereas in Indonesia, it’s still hindered by structural and cultural factors. The research extends the TAM by integrating culture and border context in fintech adoption. Practically, this study emphasizes the need for digital and financial literacy supported by infrastructure for MSME actors. The government also needs to promote inclusive and collaborative policies between financial institutions, fintech providers, and local communities to increase more equitable financial adoption.